2012
DOI: 10.4236/abb.2012.327129
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 1-(N-acetyl-6-aminohexyl)-3-hydroxypyridin-4-one (CM1) in treatment of iron-loaded hepatocyte cultures

Abstract: Excessive iron is toxic to cells and organelles, where it can generate harmful reactive oxygen species (ROS) resulting in oxidative tissue damage. Liver is the major organ for iron storage and redox active iron in this tissue can cause fibrosis and cirrhosis in β-thalassemia patients. Desferrioxamine (DFO), deferiprone (DFP) and deferasirox (DFX) are clinically approved iron chelators used for the treatment of patients with iron overload, but none of these chelators are completely free of side effects. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Plasma MDA level was slightly increased and hepatic MDA was markedly increased in the Fe diet-fed mice when compared to the N diet-fed mice, while liver fibrosis is likely to occur. Our recent study has demonstrated that the CM1 reduced levels of LIP in mouse hepatocyte and HepG2 cell cultures, effectively [28]. A previous study reported that reactive iron and redox ROS in the iron overloaded liver can induce fibrosis [61].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Plasma MDA level was slightly increased and hepatic MDA was markedly increased in the Fe diet-fed mice when compared to the N diet-fed mice, while liver fibrosis is likely to occur. Our recent study has demonstrated that the CM1 reduced levels of LIP in mouse hepatocyte and HepG2 cell cultures, effectively [28]. A previous study reported that reactive iron and redox ROS in the iron overloaded liver can induce fibrosis [61].…”
Section: Discussionmentioning
confidence: 94%
“…The compound was able to chelate plasma NTBI, but was not toxic to peripheral blood mononuclear cells (PBMC), cardiomyocytes and hepatocytes in vitro. Importantly, CM1 had reduction efficiency of LIP in ironloaded hepatocyte as well as in myocyte cultures [28]. In the present study, we investigated a potential role of our new chelator, CM1 in the treatment of iron-loaded mice.…”
Section: Introductionmentioning
confidence: 92%
“…Our lead compound, CM1, is a synthetic bidentate chelator that is more lipophilic than DFP and can bind the iron efficiently [ 17 ]. Interestingly, the chelator is able to chelate NTBI in thalassemic serum, but is not toxic to peripheral blood mononuclear cells, hepatocytes, and myocytes in vitro [ 20 ]. Due to the high cost of chemical drugs, we are increasingly interested in alternative therapies that employ natural products.…”
Section: Discussionmentioning
confidence: 99%
“…It also reduces plasma non-transferrin bound iron and labile plasma iron [ 18 ]. Importantly, the compound shows low toxicity [ 19 , 20 ]. However, there are published reports of this compound processing a neuroprotective effect.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel orally active iron chelator, 1-(N-acetyl-6-aminohexyl)-3-hydroxy-2-methylpyridin-4-one (CM1) has been designed [13] and preliminary results have demonstrated that the CM1 is an effective bidentate chelator which is slightly more lipophilic than the DFP. The compound has been shown to reduce iron-induced redox damage and to decrease the levels LIP in hepatocytes [14]. In the present study, we have investigated the effects of CM1 on LIP and ROS levels in primary hepatocyte and HepG2 cell cultures.…”
Section: Introductionmentioning
confidence: 97%